From Branding to Applying: The Role of Corporate Reputation as a Mediating Variable among Gen Z - Febrina, Shinta; Erlin, Nia Ariyani (Manunggal Halim Jaya, 2026)
Intention to apply is the process by which individuals begin to show interest in joining a company, particularly among Gen Z students. Gen Z has different preferences when choosing a workplace compared to previous generations. Therefore, companies must not only compete in terms of products and services but also in the recruitment process. The purpose of this study is to examine how employer branding influences Gen Z students' intention to apply in Padang City, using corporate reputation as a mediating factor. A total of 140 respondents were selected using purposive random sampling for quantitative research employing Partial Least Squares Structural Equation Modeling (PLS-SEM) as the analytical tool. The findings of this study conclude that (1) employer branding has a significant positive effect on intention to apply, (2) employer branding has a significant positive effect on corporate reputation, (3) corporate reputation has a significant positive effect on intention to apply, and (4) corporate reputation significantly mediates the effect of employer branding on intention to apply. The results of this study are expected to provide strategic recommendations for companies in Padang City to compete in attracting high-quality young talent in this digital era.